Beyond age: exploring ultimate attainment in heritage speakers and late L2 learners - Prela, Leonarda; Dąbrowska, Ewa; Llompart, Miquel (Frontiers in Psychology, 2024)
According to the Critical Period Hypothesis, successful language learning is optimal during early childhood, whereas language learning outside of this time window is unsuccessful. In this respect, early language acquisition is viewed as convergent and reliable but late acquisition is not. The present study revisits the idea of a critical period by investigating the grammatical attainment of early bilinguals/heritage speakers (HSs), late second/foreign language (L2) learners, and comparable groups of monolinguals by testing Greek-English bilinguals in the two languages they speak by means of a grammaticality judgment task. Our findings show that in English, HSs performed on par with monolinguals, both groups surpassing the late L2 learners, who performed about 2 SDs below the HSs and the monolinguals. In Greek, late L2 learners and monolinguals exhibited comparable performance, contrasting sharply with the HSs' significantly lower proficiency, which was on average about 5 SDs below the late L2 learners and the monolinguals. Consequently, our results show that the performance gaps between HSs and Greek monolinguals/late L2 learners were more pronounced than the differences between late L2 learners and English monolinguals/HSs, suggesting that the early bilinguals' success in English may come at the expense of their heritage language (Greek). Furthermore, we observe substantially more individual variation within HSs in their heritage language than within the late L2 learners for their second language. Thus, testing bilinguals in both of their languages allows us to unveil the complexity of grammatical ultimate attainment and prompt a re-thinking of age as the major determining factor of (un)successful attainment.